Suitability of Different Mealybug Species (Hemiptera: Pseudococcidae) as Hosts for the Newly Identified Parasitoid Allotropa suasaardi Sarkar & Polaszek (Hymenoptera: Platygasteridae) - Sarkar, M. A.; Suasa-ard, Wiwat; Uraichuen, Sopon (Agriculture and Natural Resources, 2014)
The parasitoid Allotropa suasaardi Sarkar & Polaszek (Hymenoptera: Platygasteridae) was recently described from a series of specimens reared from Phenacoccus manihoti Matile-Ferrero on cassava (Manihot esculenta Crantz) in a field in Kanchanaburi province, Thailand. It is currently being evaluated as a biological control agent of the cassava mealybug complex. In order to understand host/parasitoid ecological interactions and optimize the mass-production system of this parasitoid, nine mealybug species (P. manihoti, Pseudococcus jackbeardsleyi Gimpel & Miller, Ferrissia virgata (Cockerell), Phenacoccus madeirensis Green, Planococcus citri (Risso), Dysmicoccus neobrevipes Beardsley, Coccidohystrix insolita (Green), Rastrococcus spinosus (Robinson) and Paracoccus marginatus Williams & Granara de Willink) widespread in Thailand, were tested to determine their potential as alternative hosts for the parasitoid. A set of tests was conducted in the laboratory on susceptibility, preference and suitability. Successful parasitization and the development of progeny were obtained with four mealybug species, D. neobrevipes, P. manihoti, P. madeirensis and P. jackbeardsleyi; the other mealybug species were not utilized by the parasitoid. A. suasaardi accepted multiple species for development, with the ranking of species preference, from the most to the least being D. neobrevipes, P. manihoti, P. madeirensis and P. jackbeardsleyi. The mean developmental time was shorter and a higher number of progeny were produced in D. neobrevipes mealybug species followed by P. manihoti. The results presented in this study show some of the range of hosts available for A. suasaardi Sarkar & Polaszek in Thailand.